Price efficiency on Islamic banks vs. conventional banks in Bahrain, UAE, Kuwait, Oman, Qatar and Saudi Arabia: Impact of country governance - Kamarudin F.; Sufian F.; Nassir A.M.; Anwar N.A.M.; Ramli N.A.; Tan K.M.; Hussain H.I. (Inderscience Publishers, 2024)
Indexed by Scopus